Epicatechin oligomers longer than trimers have anti-cancer activities, but not the catechin counterparts - Kohki Takanashi (Nature Portfolio, 2017)
Abstract Since procyanidins (oligomeric catechin or epicatechin) were reported to exhibit health benefits, much attention has been paid to the synthesis of these compounds, especially those that are longer than trimers. In the present study, syntheses of cinnamtannin A3 (epicatechin pentamer), A4 (epicatechin hexamer), catechin tetramer, pentamer, arecatannin A2 (epicatechin-epicatechin-epicatechin-catechin) and A3 (epicatechin-epicatechin-epicatechin-epicatechin-catechin) were achieved. The key reaction was a Lewis acid mediated equimolar condensation. The antitumor effects of these synthesized compounds against a human prostate cancer cell line (PC-3) were investigated. Among the tested compounds, cinnamtannin A3, A4 and arecatannin A3, which possess epicatechin oligomers longer than tetramers as the basic scaffold, showed significant activities for suppression of cell growth, invasion and FABP5 (fatty acid-binding protein 5) gene expression. Effects on cell cycle distribution showed that cell cycle arrest in the G2 phase was induced. Furthermore, these epicatechin oligomers suppressed significantly the expression of the cancer-promoting gene, FABP5, which is related to cell proliferation and metastasis in various cancer cells. Interestingly, the suppressive activities were associated with the degree of oligomerization of epicatechin. Thus, synthetic studies clearly demonstrate that epicatechin oligomers longer than trimers have significant anti-tumorigenic activities, but not the catechin counterparts.